CHARACTERISTICS OF AEOLIAN SOLID FLOWS IN THE INTERACTION ZONE OF LAND AND SEA - Nasedkin, E.I. (Institute of Geological Sciences, NAS of Ukraine, 2014)
Results of monitoring observations of aeolian material composition and the transfer peculiarities in the land-and-sea direction within the Black Sea range of Experimental Branch of Marine Hydrophysical Institute of NAS of Ukraine are presented.